Actinidia arguta (Baby Kiwi) Waste: Preliminary Considerations on Seed Recovery - Nicole Roberta Giuggioli; Cristiana Peano; Luca Brondino (Applied Sciences, 2023)
Fruit seed oils are of new interest due to their significant properties and can be a good opportunity to recover fruit waste. Actinidia arguta (baby kiwi) fruits are a novelty in the market and berries can be consumed with the peels. Due to their limited shelf life, fruits are very perishable and the waste management techniques used post-harvest are an important issue. Berry waste can be reused, for biological flows focused on food losses and waste reduction. Therefore, baby kiwi fruit samples were collected from the Ortofruititalia company orchards in Cuneo, Italy, and then processed and analysed for seed oil constituents using standard analytical methods. The results of this study indicate that unsaturated fatty acids were the most dominant fatty acids (92.6 g/100 g) in comparison with saturated (7.4 g/100 g). In addition, α-linoleic acid (82.7 g/100 g) was the most dominant unsaturated fatty acid. Additionally, γ-Tocopherol (0.023 g/100 g) was the most dominant tocopherol in this study. Extraction of seed oil from these berries could be proposed as an option for obtaining high-added-value oils for pharmaceutical cosmetics, among other uses.